PENINGKATAN DAYA SAING UMKM DESA BLAHKIUH MELALUI PENGUATAN BRANDING DAN INOVASI KEMASAN - Udayana, Putu Suweca Nata; Martini, Luh Kadek Budi; Farhaeni, Mutria; Indrya, Dewa Ayu Giovany Angga (Universitas Mataram, 2025)
The community service conducted by STB Runata in Blahkiuh Village aims to support the preservation of local culture and increase the competitiveness of business actors through creative and collaborative approaches. This activity includes three main focuses, namely: (1) the creation of promotional content in the Subak area as an effort to preserve cultural heritage and strengthen traditional agriculture-based tourism attractions; (2) product packaging assistance to Jaje Begina MSMEs to improve the visual quality and selling value of traditional processed products; and (3) a visit to the incense medium industry to identify the potential and challenges faced by local industry players in the aspects of production and marketing. The total number of participants who attended this activity was 80 (eighty) people. The method used to solve the problems was to conduct socialization activities, training and assistance in packaging, labeling jaje begine MSME products and creating content in subak. The results of the activities showed an increase in awareness of the importance of digital promotion, packaging innovation, and the potential for developing local products based on cultural and spiritual values. This service is expected to be the first step in strengthening a sustainable local business ecosystem based on local wisdom.